Exploring Integrated Governance to Stimulate Sustainable Performance of Village-Owned Enterprises - Sari, Niki Puspita; Muhammad, Helmi; Imron, Muhammad; Azwar Anas, Muhammad Yusuf; Sutomo, Sutomo; Assiddiq, Dafis Ubaidillah; Jannah, Urnika Mudhifatul (Universitas Muhammadiyah Yogyakarta, 2024)
Good governance integration may assist Village-Owned Enterprises (BUMDes) in achieving sustainable performance. This study focused on the adoption of governance principles and their impact on sustainable performance at BUMDes Mutiara Welirang in Mojokerto, East Java, Indonesia. This study used an exploratory descriptive qualitative approach using a single case to explore the phenomenon in depth. Data collecting methods include structured interviews, field observations, focus group discussions, and document studies. The method of determining informants is divided into two stages: purposive sampling to identify important informants based on specific criteria and snowball sampling for supporting informants. Data were processed using thematic analysis to identify, analyze, and report on interview findings. The study's findings show that BUMDes Mutiara Welirang's governance procedures incorporate cooperative, participatory, emancipatory, transparent, accountable, and sustainable principles. The integration of BUMDes governance serves as the foundation for achieving sustainable performance in not only economic but also social, environmental, and cultural dimensions. This study's implications include improving the welfare of multiple stakeholders in financial, social, environmental, and organizational cultural dimensions. This study also provides theoretical benefits, such as serving as a role model for BUMDes governance in Indonesia to achieve sustainable performance.